A history of the music therapy profession : diverse concepts and practices - Byers, Kerry L. Hyrniw (Barcelona Publishers, 2016)
An introduction to music therapy concepts and practices from historical and international perspectives, with descriptions of the many models of practice and theories that have shaped the discipline since the 1930's. The book recounts the circumstances and historical precursors for establishment of today's profession, while tracing the enormous diversity of the discipline. The implications of this diversity for the future are discussed, and reccomendations are made for identifying and claiming the sole ""jurisdictions"" that are the rightful claim of music therapy.